2010
DOI: 10.1002/anie.200906291
|View full text |Cite
|
Sign up to set email alerts
|

Layered Graphene/Quantum Dots for Photovoltaic Devices

Abstract: Layering in the sun: Layered graphene and quantum dot (QD) films can be fabricated simply on transparent conducting indium tin oxide (ITO) substrates from aqueous solutions. The structure and favorable work function of graphene make it effective for the collection and transfer of photogenerated charges to the electrode, resulting in a high‐performance photovoltaic device (see picture; IPCE=incident photon‐to‐charge‐carrier conversion efficiency, SWNT=single‐walled carbon nanotube).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
141
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(144 citation statements)
references
References 33 publications
0
141
0
Order By: Relevance
“…Hybrid materials based on inorganic nanoparticles and graphene or its hydrophilic derivative, graphene oxide (GO), have been shown to significantly boost the functional performance in a wide range of applications, [3] such as heterogeneous, [4] electro- [5] and photo-catalysis, [6] energy storage, [7] CO2 adsorption, [8] and sensing. [9] This study focuses on the utilization of GO as support for two-dimensional functional nanoparticles, specifically for mixed metal oxides (MMOs) that are produced from twodimensional layered double hydroxide (LDH) nanoparticles. GO is expected to be particularly efficient as a support for LDH-derived MMOs due to the matching 2D geometry and the charge complementarity of the initial (positively-charged) LDH nanoplatelets and the exfoliated (negatively-charged) GO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid materials based on inorganic nanoparticles and graphene or its hydrophilic derivative, graphene oxide (GO), have been shown to significantly boost the functional performance in a wide range of applications, [3] such as heterogeneous, [4] electro- [5] and photo-catalysis, [6] energy storage, [7] CO2 adsorption, [8] and sensing. [9] This study focuses on the utilization of GO as support for two-dimensional functional nanoparticles, specifically for mixed metal oxides (MMOs) that are produced from twodimensional layered double hydroxide (LDH) nanoparticles. GO is expected to be particularly efficient as a support for LDH-derived MMOs due to the matching 2D geometry and the charge complementarity of the initial (positively-charged) LDH nanoplatelets and the exfoliated (negatively-charged) GO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their remarkable high electron mobility (15,000 cm 2 /V·s) [8], extremely large surface area (~2600 m 2 /g) [9], and low fabrication cost, GNs are considered as an ideal support for developing next-generation photovoltaic devices [10]. Li et al reported that on forming layered GNs-CdS quantum dots (QDs), the electrode exhibited a significant improvement in photo-response compared with that of single-walled carbon nanotube-CdS QD nanocomposites [11].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 with a size of about 7 nm fully cover both surfaces of the graphene nanosheets. The growth of TiO 2 on the surface of GO plays an important role in enhancing photocurrent response [77] and, thus, improving the photocatalytic ability. Li and coworkers [78] synthesized CdS cluster-decorated graphene nanosheets via a solvothermal method (Figure 7).…”
Section: D/0dmentioning
confidence: 99%